Sustainable phosphorous management in two different soil series of Pakistan by evaluating dynamics of phosphatic fertilizer source - Aimen, Ayesha; Basit, Abdul; Bashir, Safdar; Aslam, Zubair; Shahid, Muhammad Faheem; Amjad, Saba; Mehmood, Khadija; Aljuaid, Bandar S.; El-Shehawi, Ahmed M.; Tan, Ali Kee Zuan; Farooq, Shahid; Li, Yunzhou (Elsevier BV, 2021)
Phosphorous (P) plays the prominent role to promote the plants storage functions and structural roles, as it is recognized as a vital component of ADP, ATP, Cell wall as well as a part of DNA. Soils acts as the sink to supply P to plants because soil pH and its physical condition are the main factor which regulate the solubility and availability P element. Phosphorus is not deficient in Pakistani soils but its availability to plants is the serious matter of concern. A pot experiment was conducted to evaluate P dynamics in two different soil series of Pakistan (Bahawalpur and Lyallpur) using Maize as test crop. The treatments applied were T0: Control (without any fertilizer), T1: Recommended DAP @648 mg pot−1, T2: Half dose DAP @324 mg pot−1, T3: Recommended rate of TSP @900 mg pot−1, T4: Half dose TSP @450 mg pot−1. Soil analysis showed that Bahawalpur soil has sandy clay loam texture with 33% clay and Lyallpur series has sandy loam texture with 15.5% clay; furthermore, these soils contain 4.6 and 2.12% CaCO3, respectively. Results showed an increase in P concentration in roots (23 mg kg−1) with the application of half dose of TSP in Lyallpur series and lowest in Bahawalpur series (14.6 mg kg−1) at recommended dose of DAP. Concentration of P in shoots responded the same; increase at half dose of TSP (16.7 mg kg−1) and lowest at full dose of DAP in Bahawalpur series as (15.58 mg kg−1). Adsorbed P (17 mg kg−1) was recorded highest in Bahawalpur soil with more clay amount in pot with DAP application but lower in Lyallpur soil series (14 mg kg−1) with the application of applied TSP. The PUE was recorded highest in Lyallpur series with the application of half dose of TSP and it was 61% more than control and was Highest in Bahawalpur series was with the application of recommended dose of DAP is 72% more than control treatment. On estimation, results showed that applied sources made an increase in P availability than control, but TSP gave better P uptake than DAP unless of rates applied. Soil of Lyallpur series showed better uptake of P and response to applied fertilizers than Bahawalpur series which showed more adsorption of P by high clay and CaCO3 amount. Conclusively, the study suggested that soil series play a crucial role in choosing fertilizer source for field application.